'To Finish, We Must Finish': Everyday Practices of Depletion in Sri Lankan Export-Processing Zones. Issue 6 (1st November 2016) - Gunawardana, Samanthi J.
Abstract: The integrative dynamic between social reproduction (SR) and the market economy is underscored by the everyday experience of what can be termed 'depletion' for many women in the Global South. Drawing upon case study material from Sri Lanka, this paper focuses on migration decisions to work in export-processing zones (EPZs) and everyday production processes. It shows how workplaces are sites of depletion. Depletion reproduces the processes of disposability in global factories. Relations of SR are also reproduced in the factory. Affecting body and mind, depletion flourishes in environments without recourse to adequate inputs that maintain well-being including, but not limited to, leisure and rest, adequate wages, freedom of association, adequate nutrition, housing, and job security. In Sri Lanka, migration to EPZs was prompted by a crisis in SR and lack of inflows to sustain the well-being of women and households. Such workplaces are also an everyday day element of the global political economy, enacted upon gendered bodies, fuelling a cycle of gendered harm through the reproduction of disposability.